An Interactional Sociolinguistics Perspective - Donna DelPrete (Studies in Applied Linguistics & TESOL, 2005)
In this husband and wife’s conversation about future vacation plans, a communication struggle seems to be taking place. The interlocutors are struggling to get their respective points across through conflicting frames, differing stances, and lack of alignment with each other. The numerous pauses in each of the three excerpts, as well as the overlaps, the elongated vowels, the repeated expressions, and the emphatic stresses on words and phrases are among the contextualization cues that signal conflicting conversational frames (Tannen, 1993), and areas of communicative breakdowns. Framing is a key notion in any analysis of human interaction, particularly when analyzing discourse in terms of gender relations (Tannen, 1990). Common frames, and shared expectations, help to ensure smooth, synchronous conversational exchanges (Gumperz, 1982). When speakers are operating under different frames, lack of conversational synchronization and participant alignment are accompanying factors. From the interplay of all these factors, communication clashes are likely to arise. In the three excerpts, each speaker experiences moments of tension, discomfort, and misunderstanding due to conflicting frames and lack of shared expectations and alignment.